Inferior Vena Cava Tumour Thrombectomy by Novel Endovascular Approach - Shahril K; Reynu R; Kosai NR; Bong, JJ; Rozman Z; Yazmin; Mohd Ramzisham AR (Penerbit UKM, 2015)
The presence of thrombus within the inferior vena cava (IVC) is often a sign of advance hepatocellular carcinoma (HCC). Various treatment methods have been described with variable and inconclusive results. Now, the advancement of endovascular approach offers new possibility as a potential treatment modality.We discuss the removal of tumour thrombus with catheter directed mechanical thrombectomy. IVC tumour secondary HCC was removed by AngioJet® rheolytic system (Possis Medical, Minneapolis, MN, USA) with good result. Further work should be encouraged to explore the prospect of this technique with other treatment modalities.